2021
DOI: 10.1101/2021.05.03.442418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DELAY OF GERMINATION 6, encoding theANAC060transcription factor, inhibits seed dormancy

Abstract: The timing of seed germination is regulated by seed dormancy. There is ample natural variation for seed dormancy among as well as within plant species. In Arabidopsis several DELAY OF GERMINATION quantitative trait loci have been identified, of which DOG1 is best studied. Here we report the identification of DOG6, a quantitative trait locus with a similar strong effect on seed dormancy as DOG1. DOG6 affects the timing of germination both in laboratory as well as in field conditions. Complementation cloning rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…We scored seed dormancy in several T-DNA mutants disrupting genes associated with dormancy in our GWAS. Two alleles in ANAC60 showed enhanced dormancy when set at 22°C (Supplementary Fig.1), as recently described 16 . In the phyB region the most strongly dormancy-associated SNPs were approximately 20kb distal to the phyB gene, in a locus with two seed-expressed homologues of VIN3, VEL2 and VEL3 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
“…We scored seed dormancy in several T-DNA mutants disrupting genes associated with dormancy in our GWAS. Two alleles in ANAC60 showed enhanced dormancy when set at 22°C (Supplementary Fig.1), as recently described 16 . In the phyB region the most strongly dormancy-associated SNPs were approximately 20kb distal to the phyB gene, in a locus with two seed-expressed homologues of VIN3, VEL2 and VEL3 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
“…The identified DOG QTL underly genes of a different nature; so far DOG1 , DOG6 , and DOG18 are cloned, and these encode, respectively, an unknown protein, a NAC transcription factor, and a pseudo phosphatase (RDO5) ( Bentsink et al 2006 ; Xiang et al 2016 ; Song et al 2021 ). Although we can only speculate about the nature of the remaining DOG loci, genetic analyses and transcriptional profiling have indicated that they control dormancy by different additive genetic and molecular pathways ( Bentsink et al 2010 ).…”
Section: The Power Of Natural Variation Among Others a Dog1 Storymentioning
confidence: 99%
“…DOG6 encodes the NAC transcription factor ANAC60 ( Song et al 2021 , 2022 ). Different natural alleles of DOG6 determine the localization of the protein due to the presence or absence of a membrane binding domain.…”
Section: The Power Of Natural Variation Among Others a Dog1 Storymentioning
confidence: 99%
“…Temperature, light, relative humidity, and nutrients are major exogenous factors which indirectly regulate seed dormancy by affecting endogenous factors (Basbouss-Serhal et al, 2016). The characterization of several other key dormancy regulatory factors in seed plants have enriched our understanding of seed dormancy supervision, such as DELAY OF GERMINATION1 (DOG1) (Bentsink et al, 2006;Carrillo-Barral et al, 2020), REDUCED DOR-MANCY 5/DELAY OF GERMINATION18 (RDO5/DOG18) (Xiang et al, 2014(Xiang et al, , 2016, DELAY OF GERMINATION 6/ ANAC060 (DOG6) (Song et al, 2021), Arabidopsis thaliana SEED DORMANCY4-LIKE/REVERSAL OF RDO5 1(AtSdr4L/ ODR1) (Cao et al, 2020;Liu et al, 2020), ETHYLENE RE-SPONSE1/REDUCED DORMANCY3 (ETR1/RDO3) (Li et al, 2019) and LEUCINE ZIPPER TRANSCRIPTION FACTOR67 (bZIP67) (Bryant et al, 2019) from Arabidopsis; Sdr4 (Sugimoto et al, 2010), and MOTHER OF FT AND TFL2 (MFT2) (Song et al, 2020) from rice; mitogen-activated protein kinase kinase 3 (MKK3) from barley (Nakamura et al, 2016) and wheat (Torada et al, 2016); and alanine aminotransferase (AlaAT) from barley (Sato et al, 2016).…”
Section: Introductionmentioning
confidence: 99%